2006
DOI: 10.1289/ehp.8781
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene Exposure during Cardiac Valvuloseptal Morphogenesis Alters Cushion Formation and Cardiac Hemodynamics in the Avian Embryo

Abstract: It is controversial whether trichloroethylene (TCE) is a cardiac teratogen. We exposed chick embryos to 0, 0.4, 8, or 400 ppb TCE/egg during the period of cardiac valvuloseptal morphogenesis (2–3.3 days’ incubation). Embryo survival, valvuloseptal cellularity, and cardiac hemodynamics were evaluated at times thereafter. TCE at 8 and 400 ppb/egg reduced embryo survival to day 6.25 incubation by 40–50%. At day 4.25, increased proliferation and hypercellularity were observed within the atrioventricular and outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 47 publications
8
40
0
Order By: Relevance
“…Additionally, the time-course experiments confirmed the results obtained with the 10 ppb TCE exposure (24 h) and indicated that exposure to low concentrations of TCE exerts a long-lasting effect (at least 72 h) on expression levels of the tested genes. Overall, our results are in agreement with data recently published by Drake et al [8,42] and Mishima et al [9] reporting that the effects of TCE on chick cardiac development were dose-and stage-specific. Importantly, our observed alterations in gene expression level between 1 and 10 ppb TCE are consistent with Drake's reported effects on valvuloseptal hypercellularity and reduced hemodynamics in chick embryos exposed to 8 ppb TCE.…”
Section: Real-time Pcr Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, the time-course experiments confirmed the results obtained with the 10 ppb TCE exposure (24 h) and indicated that exposure to low concentrations of TCE exerts a long-lasting effect (at least 72 h) on expression levels of the tested genes. Overall, our results are in agreement with data recently published by Drake et al [8,42] and Mishima et al [9] reporting that the effects of TCE on chick cardiac development were dose-and stage-specific. Importantly, our observed alterations in gene expression level between 1 and 10 ppb TCE are consistent with Drake's reported effects on valvuloseptal hypercellularity and reduced hemodynamics in chick embryos exposed to 8 ppb TCE.…”
Section: Real-time Pcr Analysissupporting
confidence: 94%
“…Recently, the National Academy of Sciences issued a report [7] suggesting TCE exerts negative effects on cardiac development, particularly in avian models. In addition, two groups provided independent observations indicating that TCE specifically alters endocardial cushion formation in chick embryos [8,9]. These results are in line with previous data obtained from Boyer et al [10], suggesting that TCE disrupts the endothelial mesenchymal transition (EMT), a process involved in formation of the endocardial cushion in chick embryos.…”
Section: Introductionsupporting
confidence: 87%
“…Data has demonstrated that the earliest embryonic expression of phase I detoxification enzymes is in the developing heart, and expression of these CYPs is relevant to the susceptibility of the developing heart to environmental teratogens [37]. Any perturbation of cardiac function contributes to the etiology of congenital heart defects in TCEexposed embryos, while the ventricular septal defect induced by TCE may be secondary to functional impairments that alter cardiac hemodynamics and subsequent ventricular foramen closure, which is consistent with recent demonstrations that TCE impairs calcium handling in cardiomyocytes [39][40][41]. DNA microarray technology was used to profile gene expression in embryonic mouse hearts with low-dosage TCE exposure, which caused extensive alterations 7.…”
Section: Discussionsupporting
confidence: 83%
“…Exposure to TCE has also been associated with increased incidence of congenital heart malformations [4,18,39], although past studies have reported inconsistent results [1,4,15], mainly due to differences in experimental conditions. However, recent data from our and other groups [9,13,14,30,33] have supported the notion that exposure to low, environmentally significant doses of TCE affects physiological heart development in both rodent and chick models. In particular, studies using in vitro and in vivo systems [8,9,34] documented that TCE impaired calcium handling in cardiomyocytes, which is controlled largely by the calcium ATPase, Serca2a.…”
Section: Introductionsupporting
confidence: 52%